You and Me Got a Whole Lot of History: an historical analysis of music distribution and formats, and the socio-cultural trends that have shaped them - Jamieson, Brianna Maree (Auckland University of Technology, 2016)
The music industry has been in a state of flux for the past 20 years. Disrupted by the digital revolution, and the significant consumer uptake in the piracy of music product, revenues have fallen substantially over a relatively short period of time. This case study analyzes the historical timeline of music product formats and distribution methods whilst contextualizing them through the socio-cultural trends that have shaped the shifts in music format and distribution methods, through a business lens. From the distribution of physical music product, through all the transitional periods surrounding the digital revolution, and the new model of non-acquisition consumption through streaming, the consumer behaviour trends that have impacted on music distribution and format are analyzed as important influencing factors. The case study uncovers an industry resistant to change, and an industry that behaves in a wholly reactive way to consumer behaviour trends. This research also discusses the potential future around the sale of recorded music, as socio-cultural trends continue to shape the development of music as a cultural commodity. A distribution strategy for maximizing revenue for each distribution method and format is proposed, by strategically releasing new recorded music products (albums) physically, digitally and through streaming service in a specific timeline in order to avoid the cannibalization of each format. It is further proposed that the future of recorded music may not actually lie in the sale of recorded music being a primary revenue stream for the music industry going forward, and instead may be more appropriately utilized as a marketing vehicle to drive consumer spending in more lucrative revenue streams such as live performance, and branded merchandise. (Also, the title is a One Direction lyric).
Keywords: Marketing; Consumer behaviour; Socio-cultural trends; Historical analysis; Case study; Historical case study; Music industry; Music; Music product; Music as a commodity; Record labels; Record label; Major record labels; Major record label; Digital music; Streaming; Spotify; Distribution; Music format; Music distribution; Music revenue; Digitization; Digital revolution